The use of point‐of‐care ultrasound to diagnose infective endocarditis causing an NSTEMI in a patient with chest pain. Issue 2 (6th February 2020) - Cohen, Allison; Greco, Jeff; Levitus, Matthew; Nelson, Mathew
Abstract: Infective endocarditis is a severe condition that requires rapid identification and treatment. Early diagnosis is often difficult due to diverse and often vague presenting symptoms. One uncommon complication is acute coronary syndrome that can be secondary to dissemination of septic emboli. Although rare, this coronary complication is life threatening and associated with increased mortality. Point‐of‐care ultrasound (POCUS) is a useful diagnostic modality in patients with suspected endocarditis because it can attempt to identify vegetations and evidence of cardiac ischemia by identifying regional wall motion abnormalities. The following case demonstrates a patient with infective endocarditis causing a non‐ST elevation myocardial infarction diagnosed in the emergency department using POCUS.